Manajemen Program Kelas Cerdas Istimewa dan Bakat Istimewa dalam Meningkatkan Prestasi Siswa Menuju PTN, Madrasah Aliyah Amanatul Ummah Pacet Mojokerto - Ahmad Khotib (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
As an effort to optimize the quality of human resources, the role of education has never been spared in producing forward-thinking human resources along with the development of the times. Where this is a very extraordinary thing to improve student achievements, both academic and non-academic. Madrasah Aliyah Amanatul Ummah Special Intelligent Class Program for Special Talents is considered to have been maximized in improving achievement in students, so that they are able to go to university, this has been proven by the existence of students who are accepted at their favorite universities, even the Middle East and Europe. This study uses a qualitative type of research with a case study approach. The object of this research was carried out at Madrasah Aliyah Amanatul Ummah Special Intelligent Class Program for Special Talents, Data collection techniques using observation, interviews and documentation, Data analysis techniques using Milles Huberman with three stages, namely data condensation, data presentation, describing and verifying conclusions. The validity of the data used is perseverance in observation, extending research time in the field and triangulation of techniques and sources. The results of this study show that there are two ways to manage the special intelligent class program for special talents in improving student achievement: 1) Opening an olim class program. 2) The dauroh system, of these two systems, is very influential to increase the achievement of students, which of the students will be ready if there is an efent of the competition which later from the competition will get a certificate, then the certificate is used for one of the students to enter college.